Decision of the direct position problem of the joint relative manipulation mechanism with five degrees of freedom - Pashchenko, Vasilij Nikolaevič; Meleshchenko, D.I.; Rashoyan, Gagik; Malyshev, Dmitry I.; Kuzmina, Victoria S. (Zielona Góra: Uniwersytet Zielonogórski)
One of the mechanisms of joint relative manipulation with five degrees of freedom is considered. An approach to solving the direct positional problem is described. A simplified 3D model was created to verify the correctness of the solution. The results of a comparison of calculated and experimental data are presented.
Keywords: biomechanics; elasticity; plasticity; vibrations; mechanics of structures; mechatronics; plates & shells; magnetohydrodynamics; rheology; thermodynamics; tribology; fluid dynamics